Quarantine host range testing of Pseudophilothrips ichini, a potential biological control agent of Brazilian peppertree, Schinus terebinthifolia, in North America and Hawaii. Issue 2 (26th November 2016) - Wheeler, Gregory S.; Manrique, Veronica; Overholt, William A.; McKay, Fernando; Dyer, Kirsten
Abstract: Brazilian peppertree, Schinus terebinthifolia Raddi (Anacardiaceae), is an invasive weed of natural and agricultural areas of Florida, Hawaii, and Texas (USA). Biological control presents an environmentally safe and cost‐effective control method for invasive populations of this weed. Though many potential agents have been tested for specificity, nearly all have been rejected due to a broad host range. However, one species, a thrips Pseudophilothrips ichini (Hood) (Thysanoptera: Phlaeothripidae), shows promise from field observations and quarantine host range tests. A series of no‐choice, choice, and multiple‐generation tests was conducted on 127 plant taxa (including five mango and four pistachio varieties) from 45 families and 33 orders. In no‐choice starvation tests, the thrips fed and produced offspring on the target weed (124 F1 adults per plant), whereas no or few (<4 F1 adults per plant) were obtained on non‐target species. The primary exception was another exotic invasive tree Schinus molle L., on which an average 20 F1 thrips adults were produced. No‐choice tests indicated that small numbers of F1 offspring were produced on nine other non‐target plant species. The numbers of F1 offspring produced on these plants were <3% of those produced on the target weed. In choice tests, on average two or fewer F1 adults were produced on four non‐target species tested, compared with 64 F1 adults on the target weed. Multiple‐generation tests indicated that three generations of thrips were maintained only on the target weed and S. molle with no differences between these two plant species or across generations. Thus, this thrips species has a narrow host range that includes the two invasive Schinus spp. tested here. If released, the thrips P. ichini will constitute safe and potentially effective biological control of Brazilian peppertree in North America and Hawaii.